Representations of science and technology in Brazilian anarchism: José Oiticica and Maria Lacerda de Moura - Queluz, Gilson Leandro (Circumscribere International Journal for the History of Science, 2011)
This article aims at analyzing the representations of science and technology present in works by some Brazilian anarchist thinkers in the first decades of the 20th century. A tension between adoption or rejection of deterministic views on science, between enthusiasm with and critical distrust of progress, as well as an exaltation of the technical and collaborative ability of workers were present in classic anarchism writings. We intend to show how conflicting representations of science and technology were expressed in a plural way in texts of libertarian trend within the context of conservative modernization in Brazilian Old Republic. These representations include the proposal of an anarchist social energetics by José Oiticica, and the strong criticism to “bourgeois science” and technology by Maria Lacerda de Moura.